Using Escape Rooms for Conducting Team Research: Understanding Development, Considerations, and Challenges. (August 2020) - Cohen, Tara N.; Griggs, Andrew C.; Keebler, Joseph R.; Lazzara, Elizabeth H.; Doherty, Shawn M.; Kanji, Falisha F.; Gewertz, Bruce L.
Background. Modern organizations are increasingly reliant on teams, and many organizations are subsequently concerned with the development of interventions that can improve the performance of teams.Escape rooms are beginning to receive attention as a potential avenue to facilitate team-based research. Escape rooms areteam-based recreational activities that require a team of individuals to work together and think critically in order to solve a series of puzzles or challenges to escape a room. Purpose. This article provides considerations for researchers and organizations alike concerning the development of an escape room for team-based research, itsmethodological applications, andchallenges associated with the use of escape rooms in research. Developmental considerations include issues such as an escape room's location and size, financial considerations, theme development, other characteristics of the escape room, the development of puzzles and challenges, prototyping efforts, and the development of hints. Conclusion. Research considerations include the use of observational and survey methods in data collection, measurement of team processes and team performance, and how elements of an escape room influenceteamwork andproblem solving . Various challenges associated with the use of escape rooms in team-based research include considerations for dealing with cheating behavior, providing hints to participants, and resetting the room between experimental trials.